Pelatihan Pembuatan Pakan Ikan Gabus (Channa striata), serta Manajemen Usaha dan Pemasaran Produk Budidaya pada Pokdakan Maju Bersama Mesuji, Kabupaten Mesuji, Lampung - Sarida, Munti; Fidyandini, Hilma Putri; Pandjaitan, Dorothy Rouly Haratua; Yuliansyah, Ari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The purpose of this community service activity is to improve the knowledge and skills of snakehead fish farmers in Sungai Badak Village, Mesuji District, Mesuji Regency, concerning the production of fish feed based on non-fishmeal ingredients, as well as business management and business planning in fish farming. The implementation method of the activity consists of several stages: preparation and coordination, implementation, monitoring, evaluation, and follow-up assistance. A focus group discussion (FGD) activity is conducted in the preparation and coordination stage. The implementation involves delivering materials and hands-on practice in independently producing snakehead fish feed using distillers, dried grains with solubles (DDGS) and taurine, and business management and marketing strategies for cultivation results. The monitoring stage involves technical guidance on using the feed produced in their business. Finally, the evaluation stage is conducted by filling out a questionnaire related to the technology transfer provided in the community service activity and following up with assistance in processing fisheries' products and water quality management to maintain continuous and high-quality production. The evaluation results indicate an improvement in the knowledge and skills of Pokdakan members regarding the materials provided during the community service activity, with an average increase of 30%. It is noted that Pokdakan members can independently produce fish feed and plan for further fish farming business. The hope is that Pokdakan members can continue the sustainability of the counseling and training results to produce snakehead fish with self-made feed. This activity aims to stimulate Pokdakan members to improve family economics. Additionally, in the future, it aims to establish Mesuji as a center for fish farming and establish a snakehead fish village in Sungai Badak Village, supporting food availability in Mesuji Regency.